2021
DOI: 10.3389/fmicb.2021.689658
|View full text |Cite
|
Sign up to set email alerts
|

Coxsackievirus A16 in Southern Vietnam

Abstract: Background: Hand, Foot and Mouth Disease (HFMD) is a major public health concern in the Asia-Pacific region. Most recent HFMD outbreaks have been caused by enterovirus A71 (EV-A71), coxsackievirus A16 (CVA16), CVA10, and CVA6. There has been no report regarding the epidemiology and genetic diversity of CVA16 in Vietnam. Such knowledge is critical to inform the development of intervention strategies.Materials and Methods: From 2011 to 2017, clinical samples were collected from in- and outpatients enrolled in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…Similar studies in a day-care centre in Sydney, Australia, and in Viet Nam also identified CV-A16. ( 4 , 5 ) The signs and symptoms of the cases were similar to those in other HFMD outbreaks. The mild signs and symptoms reported by the cases concur with the mild and self-limiting signs and symptoms of coxsackievirus infection compared with infection with other types of enterovirus.…”
Section: Discussionsupporting
confidence: 75%
“…Similar studies in a day-care centre in Sydney, Australia, and in Viet Nam also identified CV-A16. ( 4 , 5 ) The signs and symptoms of the cases were similar to those in other HFMD outbreaks. The mild signs and symptoms reported by the cases concur with the mild and self-limiting signs and symptoms of coxsackievirus infection compared with infection with other types of enterovirus.…”
Section: Discussionsupporting
confidence: 75%
“…Hand, foot, and mouth disease (HFMD) was first described in New Zealand in 1957 and is a common childhood infectious illness (Nhu et al, 2021). It is prevalent worldwide and occurs mainly in children under 5 years of age (Xing et al, 2014;Ji et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The genetic evolution of EV-A71 virus can be divided into seven genotypes (A–G), with genotypes B and C further divided into sub-genotypes B1–B5 and C1–C5, respectively ( Brown et al, 1999 ). CVA16 is divided into 2 major genogroups A and B with genogroup B being further divided into B1 and B2 ( Nhu et al, 2021 ). Sub-genotype B1 can be further divided into clusters B1a, B1b, and B1c.…”
Section: Discussionmentioning
confidence: 99%